Communications for Development of Water, Sanitation, and Infrastructure Projects - World Bank (Washington, DC, 2014)
Ten years after the World Bank institutionalized the use of Communications for Development, the Water and Sanitation Program for Latin America and the Caribbean and the World Bank office in Peru held the 'constructive dialogue: communications for development of water, sanitation, and infrastructure projects in Latin America' workshop on November 23-25, 2009. This workshop aimed to equip participants from 21 countries in the region with tools and methods for effective communications for development within the scope of water and sanitation program for Latin America and the Caribbean projects. By summarizing the content and lessons learned from this workshop and its full report, this briefing aims to promote a deeper understanding of this field.